Combining affinity purification and mass spectrometry to define the network of the nuclear proteins interacting with the N-terminal region of FMRP - Kieffer, Félicie; Hilal, Fahd; Gay, Anne-Sophie; Debayle, Delphine; Pronot, Marie; Poupon, Gwénola; Lacagne, Iliona; Bardoni, Barbara; Martin, Stéphane; Gwizdek, Carole (Frontiers in Molecular Biosciences, 2022)
The Fragile X-Syndrome (FXS) represents the most common inherited form of intellectual disability and the first monogenic cause of Autism Spectrum Disorders. In most of cases, this disease results from the absence of expression of the protein FMRP encoded by the FMR1 gene (Fragile X messenger ribonucleoprotein 1). FMRP is mainly defined as a cytoplasmic RNA-binding protein regulating the local translation of thousands of target mRNAs. Interestingly, FMRP is also able to shuttle between the nucleus and the cytoplasm. However, to date, its roles in the nucleus of mammalian neurons are just emerging. To broaden our insight into the contribution of nuclear FMRP in mammalian neuronal physiology, we identified here a nuclear interactome of the protein by combining subcellular fractionation of rat brains with pull down affinity purification and mass spectrometry analysis. By this approach, we listed 55 candidate nuclear partners. This interactome comprises known nuclear FMRP-binding proteins as Adar or Rbm14 as well as several novel candidates, notably Ddx41, Poldip3 or Hnrnpa3 that we further validated by target specific approaches. This unique dataset includes factors involved in different steps of mRNA biogenesis, as transcription, splicing, editing or nuclear export, revealing a potential central regulatory function of FMRP in the biogenesis of its target mRNAs. Therefore, our work considerably enlarges the nuclear proteins interaction network of FMRP in mammalian neurons and lays the basis for exciting future mechanistic studies deepening the roles of nuclear FMRP in neuronal physiology and the etiology of the FXS.